Financial Inclusion and its Determinants: A Study of Bangladesh - Nur Alam Siddik, Md.; Sun, Gang; Kabiraj, Sajal (Indian Journal of Finance, 2015)
Despite the present focus of policies devoted to promote financial inclusion in Bangladesh, the issue of its comprehensive and robust measurement, which can be used to assess the extent of financial inclusion across the country is outstanding. This study attempted to fill this gap first, by proposing a multi-dimensional index and then identifying the determinants of financial inclusion. Following similar methodology used to construct the Human Development Index (HDI), data on several dimensions of financial inclusion were used to develop an index lying between 0 and 1. The Euclidean distance formula was applied to extract the normalized indicators. The findings of the study showed that only one district in Bangladesh, that is, Dhaka achieved high stated financial inclusion, and five districts achieved medium stated financial inclusion during 2009-2013, while very low financial inclusion was observed across the remaining 58 districts out of 64 districts of Bangladesh. The empirical findings also showed that 47 districts out of 64 witnessed an improvement in the IFI score of financial inclusion. However, the extent of progress of financial inclusion in these 47 districts was found to be insignificant to change their status from low financial inclusion to medium or high financial inclusion. Among the socio-geographic variables, rural population, household size, and literacy rate; among the infrastructure variables, paved road networks, Internet ; and among the banking variables, deposit penetration were found to be the significant determinants of financial inclusion. One of the major contributions of this study is that it will invoke the governments and policy makers across the world to develop a financial inclusion index for their respective countries, and thereby undertake such policies to promote financial inclusion.